IFNL4 polymorphism effects on outcome of simeprevir, peginterferon, and ribavirin therapy for older patients with genotype 1 chronic hepatitis C. Issue 3 (21st April 2016) - Mori, Nami; Imamura, Michio; Kawakami, Yoshiiku; Nagaoki, Yuko; Kawaoka, Tomokazu; Tsuge, Masataka; Hiramatsu, Akira; Hayes, C. Nelson; Aikata, Hiroshi; Miki, Daiki; Ochi, Hidenori; Honda, Yohji; et al.
Abstract : Aim: Older patients with chronic hepatitis C have a lower virological response to interferon (IFN)‐based treatments compared to younger patients. A single nucleotide polymorphism in the IFN‐λ‐4 ( IFNL4 ) gene has a potent predictive effect on treatment response to IFN‐based treatments. The efficacy of simeprevir (SMV) plus pegylated‐IFN (PEG‐IFN) and ribavirin therapy and the predictive value of IFNL4 on the outcome of therapy for older patients have not been addressed. Methods: This retrospective multicenter study included 234 consecutive Japanese patients with genotype 1 chronic hepatitis C. We assessed the predictive factors for sustained virological response (SVR) to SMV, PEG‐IFN, and ribavirin triple therapy in 170 younger (<70 years) and 64 older (≥70 years) patients. IFNL4 polymorphism ss469415590 was analyzed by Invader assay. Results: The SVR rate for older patients was similar to that for younger patients (63.9% and 72.0%, respectively). The SVR rate for the IFNL4 TT/TT group was significantly higher than the IFNL4 TT/ΔG or ΔG/ΔG group both in younger (93.6% and 46.1%, respectively, P  < 0.01) and older patients (84.4% and 33.3%, respectively, P  < 0.001). In multivariate regression analysis, IFNL4 TT/TT genotype, response to previous treatment and IFNL4 TT/TT genotype were identified as independent predictive factors for SVR in older and younger patients, respectively. Decrease in hemoglobin level was similar between the two groups. Conclusion: The virological response to SMV triple therapy in older patients was similar to that of younger patients. Analysis of IFNL4 polymorphisms is a valuable predictor in both younger and older patients.